Karakteristik Tepung Pisang dari Buah Pisang Khas Kalimantan Timur dengan Umur Simpan yang Berbeda: Karakteristik Tepung Pisang - Sadikin, Ali; Rusmini (Politeknik Pertanian Negeri Samarinda, 2023)
Banana flour is generally made from unripe bananas. However, capacity Production is often not comparable to the amount of banana production overflow, resulting in delays in the processing process. The purpose of this research is to determine the effect of different types of bananas and shelf life on the characteristics of bananas as raw materials making raw banana flour and characteristics of raw banana flour as well find out the shelf life of several types of bananas after a fruitful harvest the best characteristics of banana flour. The environmental design used in this research was a Randomized Block Design (RAK) while the treatment design was a Split-Plot Design where the main plot was a type of banana (A) which consisted of 3 levels while the sub plot was the storage time (B). which consists of 6 levels. The test is continued with the DMRT Test (Duncan Multiple Range Test) and if there is no real effect, but the single treatment has a real and/or very real effect, it is continued with the Least Significant Difference Test (BNT). The results of the research show that the shelf life of bananas to be used as banana flour is up to 3 days of storage. The shape of banana granules from 3 types of bananas, namely kapok, cotton and awa bananas and with banana storage times of 0, 1, 2, 3, 4 and 5 days shows no different shapes and sizes. The lowest banana water content is in cotton banana flour